SIMBOL DALAM KAIN ULOS PADA SUKU BATAK TOBA - Inestya Fitri Desiani (Universitas Lancang Kuning, 2022)
One of the tribes found in the western region of Indonesia, specifically North Sumatra, is the Batak Toba tribe. The Batak Toba tribe is one of the tribes which likes to do the weaving culture, making it one of the local wisdoms for the Batak Toba tribe, namely ulos cloth. Ulos is a traditional cloth obtained through a weaving process carried out by Batak women, producing various patterns. Each ulos cloth symbolizes a different message depending on the type and purpose of making the ulos cloth. The symbol carried by the ulos cloth is reflected in the patterns, patterns, and colors of the ulos cloth made on Martonun Ulos. Therefore, the types and meanings of each type of ulos cloth symbolize something from local wisdom for the Batak Toba tribe. The ulos cloth of the Batak Toba tribe symbolizes several meanings: ulos ragi hotang is usually used to ulos someone with the hope that God will give him the best results, and that person will be diligent in working. Ulos ragi is alive with colors, paintings, and patterns (ragi). giving the impression as if ulos is alive, so people call it live ragi, which is a symbol of life. Ulos sibolang with the ulosi procession is intended so that he is always careful with his family friends, and understands who should be respected, pays respect to all relatives of the wife's side, and as a sign of respect for his services while being the wife of the deceased. The local wisdom of ulos traditional weaving is an ancestral heritage that has high value and can strengthen national identity and identity that needs to be preserved by all parties to maintain the nation's cultural wealth.